2001
DOI: 10.1046/j.1365-2567.2001.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant effects of CpG oligodeoxynucleotides on responses against T‐independent type 2 antigens

Abstract: Oligodeoxynucleotides containing CpG motifs (CpG-ODN) are potent in vitro B-cell activators and they have been successfully used to increase in vivo antibody responses to T-dependent peptide and protein antigens. In contrast, the use of CpG-ODN to enhance in vivo antibody responses to various T-independent type 2 (TI-2) antigens has recently generated contradictory results. In this study, we compared the CpG-ODN stimulatory effect on antibody responses of adult and young BALB/c mice to trinitrophenylaminoethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Note that in their report, the researcher only tested coadministration of the CpG ODNs with the PS vaccine. 21 By contrast coadministration of Pneumovax with the TLR4 agonist, monophosphoryl lipid A, has been shown to enhance the antibody response in adult and aged mice. 30 From a mechanistic point of view, the reason why TLR agonists require to be administrated at least 1 day after immunization to exert their adjuvant effects remains an open question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in their report, the researcher only tested coadministration of the CpG ODNs with the PS vaccine. 21 By contrast coadministration of Pneumovax with the TLR4 agonist, monophosphoryl lipid A, has been shown to enhance the antibody response in adult and aged mice. 30 From a mechanistic point of view, the reason why TLR agonists require to be administrated at least 1 day after immunization to exert their adjuvant effects remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…In a coadministration protocol, CpG ODNs have been reported to amplify the Ab response to PS-protein conjugates 19,20 or to NP-Ficoll but not to a plain PS vaccine. 21 To reconsider the effect of TLR agonists on TI B-cell responses, we conducted experiments in which CpG1668 was administrated subcutaneously before immunization, at the time of immunization, or after immunization with PS3. The anti-PS3 IgM response was not affected when CpG1668 was injected 1 day before PS3 immunization but was consistently inhibited when PS3 and CpG1668 were coinjected ( Figure 1A).…”
mentioning
confidence: 99%
“…It has been shown that adjuvants not only can improve the immunogenicity of conjugate vaccines but also can direct the antipolysaccharide antibody isotype switch toward the desired IgG subclasses (80,81). CpG ODN 1826 (82) was shown to enhance the isotype switching from IgM to IgG2a and IgG3 subclasses for pneumococcal conjugates in a serotype-and mouse age-dependent manner (43,80,83). In our study, CpG ODN 1826 failed to significantly improve the immunogenicity of the S. suis type 2 CPS mixed conjugate or to induce isotype switching.…”
Section: Figmentioning
confidence: 99%
“…Conditions differing from those used in this study, such as the vaccine and adjuvant doses, might explain the observed differences. The biochemical properties of different CPSs might also influence the adjuvant capacity of CpG (83). As such, the choice of adjuvant is vital to maximize isotype switching.…”
Section: Figmentioning
confidence: 99%
“…An effective way of generating cellmediated immunity is by DNA-based immunization. Numerous approaches are available for enhancing DNA-based immune responses, including the coadministration of cytokine expressing plasmids (9,14), the use of immunostimulatory DNA sequences (15), the use of Salmonella vectors (32), and targeting of DNA to dendritic cells (33). In our previous studies with DNA-based immunization against HBV (18) and HCV (20), we found that the use of a recombinant poxvirus as a booster months after immunization with DNA produced a much stronger booster effect than that obtained when DNA was used as a booster.…”
mentioning
confidence: 99%